Impact of Human Capital-Based Service Quality: A Comparative Study of Visit Levels Before and After HR Optimization - Imalinda Deryane; Ezky Tiyasiningsih; Mutiara Maulina Arzakiyah (SAFE-Network, 2026)
This research investigates the strategic impact of human resource capacity building on patron engagement through a comparative analytical framework. Employing a quantitative methodology with an action research design, the study evaluates the efficacy of managerial interventions at the Bintan Regency Library. The empirical analysis was conducted on visit statistics from 80 sample units, utilizing the Paired Sample T-Test to measure comparative outcomes post-intervention. The findings demonstrate a substantial increase in visit volumes, evidenced by a mean growth of 3.80 points, representing a 131.03% escalation. Statistical verification yielded a significance value of 0.000, confirming the acceptance of the alternative hypothesis. This study concludes that the optimization of human capital serves as a critical determinant in enhancing institutional performance and fostering a dynamic public literacy ecosystem.